STING Suppresses Mitochondrial VDAC2 to Govern RCC Growth Independent of Innate Immunity. Issue 3 (29th November 2022) - Zhu, Zhichuan; Zhou, Xin; Du, Hongwei; Cloer, Erica W.; Zhang, Jiaming; Mei, Liu; Wang, Ying; Tan, Xianming; Hepperla, Austin J.; Simon, Jeremy M.; Cook, Jeanette Gowen; Major, Michael B.; et al.
Abstract: STING is an innate immune sensor for immune surveillance of viral/bacterial infection and maintenance of an immune‐friendly microenvironment to prevent tumorigenesis. However, if and how STING exerts innate immunity‐independent function remains elusive. Here, the authors report that STING expression is increased in renal cell carcinoma (RCC) patients and governs tumor growth through non‐canonical innate immune signaling involving mitochondrial ROS maintenance and calcium homeostasis. Mitochondrial voltage‐dependent anion channel VDAC2 is identified as a new STING binding partner. STING depletion potentiates VDAC2/GRP75‐mediated MERC (mitochondria‐ER contact) formation to increase mitochondrial ROS/calcium levels, impairs mitochondria function, and suppresses mTORC1/S6K signaling leading to RCC growth retardation. STING interaction with VDAC2 occurs through STING‐C88/C91 palmitoylation and inhibiting STING palmitoyl‐transferases ZDHHCs by 2‐BP significantly impedes RCC cell growth alone or in combination with sorafenib. Together, these studies reveal an innate immunity‐independent function of STING in regulating mitochondrial function and growth in RCC, providing a rationale to target the STING/VDAC2 interaction in treating RCC. Abstract : STING is a canonical innate immune sensor triggering type‐I interferon production. Here, an innate immunity‐independent STING function in governing renal cancer cell (RCC) proliferation is reported through regulating mitochondria calcium homeostasis by binding mitochondrial calcium transporter VDAC2, as well as its therapeutic potential in treating RCC.